KARAKTERISTIK SEGITIGA LUCAS - Nurshiami, Siti Rahmah; Wardayani, Ari; Setiani, Kana Hasmi (Universitas Jenderal Soedirman, 2019)
ABSTRACT. Lucas triangle is an array of coeficients of a polynomial forming a pattern which is similar to Pascal triangle. This research studies Lucas triangle and its properties. The research results show that every row in Lucas triangle is begun by the number 1 and is ended by the number 2, the sum of the first n terms of number of 1th column is equal to the number at (n+1)th row, 2nd column. Besides, the number at nth row and (n-2)th column of Lucas triangle is (n-1)^2 for n≥2, the sum of the first n terms of number of jth column is equal to the number at (n+1)th row, (j+1)^th column for j≥1. The number of Lucas triangle is the sum of two number terms in preceded row, that is the number at (n-1)th row, (j-1)^th and the number at (n-1)th row, j^th. Then, the sum of coefficients of each n^th row of Lucas triangle is .Keywords: Pascal triangle, Lucas number, Lucas triangle. ABSTRAK. Segitiga Lucas merupakan susunan koefisien-koefisien dari suatu polinomial yang disusun membentuk pola segitiga memyerupai segitiga Pascal. Penelitian ini mengkaji segitiga Lucas dan karakteristik dari segitiga Lucas. Hasil penelitian menunjukkan bahwa, setiap baris pada segitiga Lucas diawali dengan angka 1 dan diakhiri dengan angka 2, jumlah dari n suku bilangan pertama pada kolom ke-1 sama dengan bilangan pada baris ke- kolom ke-2. Selain itu, bilangan pada baris ke- kolom ke- pada segitiga Lucas adalah untuk , jumlah n suku bilangan pertama pada kolom ke-j sama dengan bilangan pada baris ke- kolom ke- untuk . Bilangan pada segitiga Lucas merupakan penjumlahan dari dua suku bilangan pada baris sebelumnya, yaitu bilangan pada baris ke- kolom ke- dan bilangan pada baris ke- kolom ke-j. Kemudian, jumlah koefisien setiap baris ke-n pada segitiga Lucas adalah .Kata Kunci: Segitiga Pascal, Bilangan Lucas, Segitiga Lucas